Lung perfusion studies after detachable coil occlusion of persistent arterial duct - Sreeram, N (1999)
OBJECTIVE—To evaluate relative lung perfusion following complete occlusion of persistent arterial duct with detachable Cook coils. METHODS—Ductal occlusion using detachable coils was performed in 35 patients (median age 3.9 years, range 0.5 to 16; 32 native ducts, three patients with previous devices). If the duct could be crossed with a 0.035 inch guidewire and a 4 F catheter after coil implantation, a further coil was implanted. Between one and seven coils were used (median two). RESULTS—Complete ductal occlusion was confirmed by echocardiography 24 hours after the procedure in all patients. Lung perfusion scans were performed three months after the procedure in 33 of 35 patients (two older patients with a single coil each did not attend). Decreased perfusion to the left lung (defined as < 40% of total lung flow) was observed in only one patient, who had previously had a 17( )mm Rashkind umbrella implanted. There was no correlation between left lung perfusion and peak left pulmonary artery Doppler velocities (r = 0.27 and p = 0.125 for the entire group; r = 0.29 and p = 0.124 after excluding patients with previous devices). CONCLUSIONS—Coil occlusion is effective in achieving complete closure of the duct. An aggressive approach using multiple coils did not compromise perfusion to the left lung.   Keywords: arterial duct; coil occlusion; lung perfusion